2019
DOI: 10.1002/fuce.201800124
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Study on Estimating Electrochemical Mechanisms in a Polymer Electrolyte Fuel Cell During Gradual Water Accumulation

Abstract: In this study, the change of electrochemical parameters during the gradual water accumulation of a polymer electrolyte fuel cell (PEFC) are estimated using electrochemical impedance spectroscopy (EIS) measurements and an impedance model based on electrode theory during a two‐step oxygen reduction reaction (ORR). EIS measurements were carried out in a 5 cm2 H2/O2 PEFC operated under a dead‐ended configuration of the gas reactants and during gradual accumulation of water. Kramers‐Kronig evaluation demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The inductive loop showed that the electrochemical reaction was not complete, and the intermediates remained on the electrode surface. 65–67…”
Section: Resultsmentioning
confidence: 99%
“…The inductive loop showed that the electrochemical reaction was not complete, and the intermediates remained on the electrode surface. 65–67…”
Section: Resultsmentioning
confidence: 99%
“…Over this frequency range, resistance (Re­( Z )) and reactance (−Im­( Z )) were recorded and graphed as Nyquist plots: −Im­( Z ) vs Re­( Z ). All Nyquist plots show positive values of Im­( Z ) at high frequencies, which is attributed to stray inductance from electrical wiring in the measurement setup . From the measured impedance, the total conductivity was determined by the equation σ = L / RA where L is the pellet thickness measured by digital calipers after the measurement, R is the resistance obtained from the x -intercept in Nyquist plots, and A is the cross-sectional area of the pellet, which was based on the inner diameter of the die used for pellet pressing.…”
Section: Methodsmentioning
confidence: 99%
“…All Nyquist plots show positive values of Im(Z) at high frequencies, which is attributed to stray inductance from electrical wiring in the measurement setup. 48 From the measured impedance, the total conductivity was determined by the equation σ = L/RA where L is the pellet thickness measured by digital calipers after the measurement, R is the resistance obtained from the x-intercept in Nyquist plots, and A is the cross-sectional area of the pellet, which was based on the inner diameter of the die used for pellet pressing. The Hebb−Wagner polarization technique was employed to measure the contribution of Cu + to the total electrical conductivity.…”
Section: Methodsmentioning
confidence: 99%
“…9 to predict the inductive loop at low frequencies. In addition, parameters from theoretical relations reported in the literature and through a graphical interpretation of the complex plot were considered [50]. Noting that the inductor element was neglected ( = 0 in Eq.…”
Section: Inductive Loop At Low Frequencymentioning
confidence: 99%